2019
DOI: 10.4269/ajtmh.19-0060
|View full text |Cite
|
Sign up to set email alerts
|

Mass Drug Administration of Triclabendazole for Fasciola Hepatica in Bolivia

Abstract: Human infection with Fasciola hepatica leads to obstruction of the common bile duct by adult worms and disease characterized by biliary colic, epigastric pain, and nausea. Recommended treatment is a single dose of triclabendazole (TCBZ) (10 mg/kg). Because in the 1990s the Bolivian Altiplano bordering Lake Titicaca was thought to have the highest prevalence of human fascioliasis worldwide, the Bolivian Ministry of Health instituted TCBZ mass drug administration (MDA). From 2008 to 2016 (excepting 2015), one do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(26 reference statements)
0
5
0
2
Order By: Relevance
“…This program treated all the population for more than 10 years with a fixed 250 mg dose independently of age or weight. 89 A recent study by Mollinedo et al documented a reduction in Fasciola prevalence to <1% compared with 12–27% from historical data in the area where the program was implemented. 89 This experience has not been replicated in other areas and further evaluation of its effectiveness and sustainability are probably warranted.…”
Section: Treatment and Controlmentioning
confidence: 99%
“…This program treated all the population for more than 10 years with a fixed 250 mg dose independently of age or weight. 89 A recent study by Mollinedo et al documented a reduction in Fasciola prevalence to <1% compared with 12–27% from historical data in the area where the program was implemented. 89 This experience has not been replicated in other areas and further evaluation of its effectiveness and sustainability are probably warranted.…”
Section: Treatment and Controlmentioning
confidence: 99%
“…Previous studies conducted in Egypt and other hyperendemic regions reported this observation [ 29 , 36 , 59 62 ]. They might become infected by eating uncooked contaminated plants while helping their parents in farming or by drinking contaminated water while playing in drainage canals [ 63 , 64 ]. This observation has been reported in other studies conducted in several South American and Middle Eastern countries [ 32 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…En Latinoamérica se ha reportado resistencia al Triclabendazol en Chile (14) , y en zonas del norte de Perú (13) ; sin embargo, en Bolivia se ha usado en forma masiva desde el 2008 al 2016 tendiendo éxito dramático (15) . En conclusión, el estudio de un paciente con masa hepática, procedente de la sierra debe llevar a plantear en sus diagnósticos diferenciales Fasciola hepática; y se debe tener criterios clínicos, laboratoriales y/o de imágenes para pensar en esta enfermedad.…”
Section: Discussionunclassified